Review on Pervaporation: Theory, Membrane Performance, and Application to Intensification of Esterification Reaction - Ghoshna Jyoti; Amit Keshav; J. Anandkumar (Journal of Engineering)
The esterification reaction is reversible and has low yield. In order to increase the yield of reaction, it is required to simultaneously remove the product of reaction. For this membranes are the viable approach. Pervaporation membranes have success in removal of components in dilute forms. Membrane performance is represented in terms of flux, sorption coefficient, separation factor, and permeance. These factors are related to the thickness of membrane, temperature, and feed concentration. Higher flux is observed at lower membrane thickness and higher feed concentration of water and lower selectivity is observed at higher temperatures due to increased free volume, lower viscosity, and higher feed side pressure. Different factors affect the pervaporation aided esterification reactor setup such as effect of initial molar ratios of the reactants, effect of catalyst concentration, effect of membrane area, and effect of temperature. Large membrane size could provide higher surface for the transfer of acid, though the challenges of membrane rupture do surround the studies. In the present review work, we tried to collaborate the works in totality of the pervaporation design starting from the membrane behavior to the process behavior. Different prospective fields are also explored which need investigation.